Strategi Kepala Sekolah dalam Pelaksanaan Ujian Nasional Berbasis Komputer (UNBK) di Sekolah Menengah Pertama - Nurdin Nurdin; Laode Anhusadar; Herlina Herlina; Sitti Nurhalimah (Institut Agama Islam Negeri Kendari, 2021)
This qualitative case study aims to review and analyze the condition of the information and communication technology (ICT) facilities for the implementation of the computer-based national examination (UNBK), the principal's strategies in implementing UNBK, and the obstacles in implementing UNBK at one of junior high schools in Kota Kendari, Southeast Sulawesi, Indonesia. Data were collected by interview, observation and documentation. The result of data analysis revealed the lack of facilities for the implementation of UNBK in the school. The principal's strategies in implementing UNBK in the school cover various aspects, such as facilities and infrastructure, human resources, and pupil affairs. Two obstacles emerged i.e., technical and non-technical.